Chatbot Menjadi Nutriosionis; Mengexplor Potensi AI untuk Meningkatkan Konsultasi Nutrisi di Indonesia - Nur Aulia, Elsa Silvia; Jati, Gumawang; Wibowo, Indra; Muhammad, Hubbi Nashrullah; Saepudin, Epin (Jurnal Sosioteknologi, 2024)
Stunting, a significant public health issue in Indonesia, adversely affects both child development and the country's economic well-being. This study investigates how AI- powered chatbots could enhance dietary advice and lower Indonesia's stunting rates. Owing to the restricted availability of certified nutritionists and the pervasiveness of mobile devices, chatbots present a scalable and convenient means of providing customized dietary advice. To properly study this topic and provide a comprehensive understanding of the situation, this study employs a quantitative approach using surveys and statistical analysis. The results suggest that chatbots driven by AI have the potential to resolve nutritional counseling issues in Indonesia; 80% of participants have prior experience utilizing chatbots. However, user needs, cultural context, and technology constraints must all be carefully considered for successful implementation. These findings indicate that implementing AI-powered chatbots is a promising strategy to significantly reduce stunting rates in Indonesian children in the process. Future research should concentrate on the development and evaluation of culturally appropriate andevidence-based chatbot interventions for potential use.